Simulation computer controlled oven by using fuzzy logic - Che Wan Nurul Fatihah, Che Wan Fadzal (2009)
An oven is a kitchen appliance that cooks or heats food by using heat which has been converted from electric energy. By using oven, we must set the temperature for each types of food, time to finish cooking and also must always take a look to make sure the food is cook well. From this, I noticed that it will be a problem to someone who didn't know how to cook very well, busy with other works but want their food cook in the good condition. So, to overcome this situation, I propose this proposal that is simulation computer controlled oven using fuzzy logic. In this project there are three clearly different parts. First, the conceptual design of the oven and the mathematical modeling implemented in Matlab-Simulink®1, second, the application of fuzzy logic in constant the variables of temperature and relative humidity and last, the analyze of display the real graph output for temperature and relative humidity. Fuzzy logic will established the temperature control system model that focus on the fuzzy logic controller using Matlab and simulated it. It indicates that using the fuzzy logic control system can greatly control the variables of the temperature and stable it.